Vitamin D and its role in psoriasis: An overview of the dermatologist and nutritionist - Barrea, Luigi (Rev Endocr Metab Disord, 2017)
Psoriasis is a chronic immune-mediated inflammatory skin disease. Psoriasis lesions are characterized by hyper-proliferation of epidermal keratinocytes associated with inflammatory cellular infiltrate in both dermis and epidermis. The epidermis is the natural source of vitamin D synthesis by sunlight action. Recently, a role for vitamin D in the pathogenesis of different skin diseases, including psoriasis, has been reported. Indeed, significant associations between low vitamin D status and psoriasis have been systematically observed. Due to its role in proliferation and maturation of keratinocytes, vitamin D has become an important local therapeutic option in the treatment of psoriasis. To date, the successful treatment based on adequate dietary intake of vitamin D or oral vitamin D supplementation in psoriasis represent an unmet clinical need and the evidence of its beneficial effects remains still controversial. This information is important either for Dermatologists and Nutritionists to increases the knowledge on the possible bi-directional relationships between low vitamin D status and psoriasis and on the potential usefulness of vitamin D in psoriasis with the aim not only to reduce its clinical severity, but also for delineating the risk profile for co-morbidities cardiac risk factors that may result from psoriasis. In the current review, we analyzed the possible bi-directional links between psoriatic disease and vitamin D.